Characterization of Colloidal Phosphorus Species in Drainage Waters from a Clay Soil Using Asymmetric Flow Field‐Flow Fractionation - Regelink, Inge C.; Koopmans, Gerwin F.; Salm, Caroline; Weng, Liping; Riemsdijk, Willem H. (Journal of environmental quality, 2013)
Phosphorus transport from agricultural land contributes to eutrophication of surface waters. Pipe drain and trench waters from a grassland field on a heavy clay soil in the Netherlands were sampled before and after manure application. Phosphorus speciation was analyzed by physicochemical P fractionation, and the colloidal P fraction in the dissolved fraction (<0.45 μm) was analyzed by asymmetric flow field‐flow fractionation (AF4) coupled to high‐resolution inductively coupled plasma–mass spectrometry and ultraviolet diode array detector. When no manure was applied for almost 7 mo, total P (TP) concentrations were low (<21 μmol L−1), and TP was almost evenly distributed among dissolved reactive P (DRP), dissolved unreactive P (DUP), and particulate P (PP). Total P concentrations increased by a factor of 60 and 4 when rainfall followed shortly after application of cattle slurry or its solid fraction, respectively. Under these conditions, DRP contributed 50% or more to TP. The P speciation within the DUP and PP fractions varied among the different sampling times. Phosphorus associated with dissolved organic matter, probably via cation bridging, comprised a small fraction of DUP at all sampling times. Colloidal P coeluted with clay particles when P application was withheld for almost 7 mo and after application of the solid cattle slurry fraction. At these sampling times, PP correlated well with particulate Fe, Al, and Si, indicating that P is associated with colloidal clay particles. After cattle slurry application, part of DUP was probably present as phospholipids. Physicochemical fractionation combined with AF4 analysis is a promising tool to unravel the speciation of colloidal P in environmental water samples.